Amino Acid Functionalized Single−Wall Carbon Nanotubes in Thermoresponsive Drug Delivery Systems: A Computational Study. Issue 4 (30th January 2019) - Ghadari, Rahim; Kashefi, Ashkan
Abstract: In this research, a computational study was conducted to evaluate the usability of amino acid functionalized single−walled carbon nanotubes (AA−SWCNTs) in the thermoresponsive drug delivery systems. The Taxol (TXL) was used as a model lipophilic drug and temperatures of 300, 310, and 315 K were selected. At first, docking studies were carried out to find the binding mode of the TXL to the surface of AA−SWCNTs. Then, molecular dynamic studies were performed. The molecular mechanics/generalized Born surface area (MM/GBSA) approach was used to evaluate the binding energies of AA−SWCNT/TXL systems. Based on the calculated binding energies in the three mentioned temperatures, Gln−, Gly−, Pro−, and Ser−SWCNT have the ability to release the TXL by increase of temperature; the weaker van der Waals interactions at higher temperature can be regarded as the origin of such observation. From another point of view, Gln− and Ser−SWCNT showed improved solubility in the aqueous media by considering the calculated logP values. These two systems are good candidates to be used in the thermoresponsive drug delivery systems. Abstract : Binding of the Taxol to the surface of functionalized SWCNT and interactions between them were studied at different temperatures. Four of the studied structure are suggested to release the Taxol in thermoresponsive manner. Also, two of the structures were useful to improve the solubility of SWCNT, that tis important from drug delivery point of view.